2020
DOI: 10.3390/app10238614
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach for Automatic Hate Speech Detection in the Saudi Twittersphere

Abstract: With the rise of hate speech phenomena in the Twittersphere, significant research efforts have been undertaken in order to provide automatic solutions for detecting hate speech, varying from simple machine learning models to more complex deep neural network models. Despite this, research works investigating hate speech problem in Arabic are still limited. This paper, therefore, aimed to investigate several neural network models based on convolutional neural network (CNN) and recurrent neural network (RNN) to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 41 publications
0
66
0
2
Order By: Relevance
“…The processed tweets were analyzed for hate speech using the pretrained CNN model. The CNN model used in this study is based on our previous work [ 20 ] in which we addressed the problem of hate speech spread in the Arabic Twittersphere. In this study, a CNN was trained on almost 10,000 tweets that were manually labeled as hate tweets or non–hate tweets.…”
Section: Methodsmentioning
confidence: 99%
“…The processed tweets were analyzed for hate speech using the pretrained CNN model. The CNN model used in this study is based on our previous work [ 20 ] in which we addressed the problem of hate speech spread in the Arabic Twittersphere. In this study, a CNN was trained on almost 10,000 tweets that were manually labeled as hate tweets or non–hate tweets.…”
Section: Methodsmentioning
confidence: 99%
“…Abusive messages in social media is a complex phenomenon with a broad range of overlapping modes and goals [17]. Cyberbullying and hate speech are typical examples of abusive languages that researchers have put more interest on in the past few decades due to it negative impacts in our societies.…”
Section: B Related Workmentioning
confidence: 99%
“…It applies the Softmax activation function to classify the high-level features obtained from the images into various categories with labels. The common pre-trained CNNs are VGGNet- 16 Theoretically, the deeper the network, the more information can be acquired and the richer the features. However, experiments have shown that with the deepening of the network, the optimization effect may become worse, and the accuracy of the test data and training data may decrease.…”
Section: Model Architecture 1) Deep Convolutional Neural Networkmentioning
confidence: 99%
“…In the past few years, as a special type of machine learning, deep learning methods have made great progress. Nowadays, the deep learning methods have been applied in various fields [15][16][17][18][19][20][21]. As Dawei et al [20] proposed a pest identification and detection system based on transfer learning, the recognition accuracy can reach 93.84%.…”
Section: Introductionmentioning
confidence: 99%